STUDENT’S ANALYSYS OF PERCEPTION TEACHERS BILINGUAL LANGUAGE USE IN SPEAKING CLASSROOM AT MTs AL -AMIN MALANG - Elta Rizma Ifari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstarct: In the teaching and learning process, communication has become one of the key primaries between the recipient and the informer. This research used a qualitative data approach. The sample consisted of 30 students in the eighth grade that separated A and B class at MTs Al-Amin Malang. The data was collected by using a questionnaire and interview. The findings of this research is this study proves that students' positive perceptions of using bilingual-based materials as language teaching in English classes. The amount of this statement reached a percentage of 86.6% of students. The most answer is